Strengthening health workforce capacity through work-based training - Matovu, Joseph KB (BioMed Central, 2013)
BACKGROUND: Although much attention has been given to increasing the number of health workers, less focus has been directed at developing models of training that address real-life workplace needs. Makerere University School of Public Health (MakSPH) with funding support from the Centers for Disease Control and Prevention (CDC) developed an eight-month modular, in-service work-based training program aimed at strengthening the capacity for monitoring and evaluation (M&E) and continuous quality improvement (CQI) in health service delivery. METHODS: This capacity building program, initiated in 2008, is offered to in-service health professionals working in Uganda. The purpose of the training is to strengthen the capacity to provide quality health services through hands-on training that allows for skills building with minimum work disruptions while encouraging greater involvement of other institutional staff to enhance continuity and sustainability. The hands-on training uses practical gaps and challenges at the workplace through a highly participatory process. Trainees work with other staff to design and implement ‘projects’ meant to address work-related priority problems, working closely with mentors. Trainees’ knowledge and skills are enhanced through short courses offered at specific intervals throughout the course. RESULTS: Overall, 143 trainees were admitted between 2008 and 2011. Of these, 120 (84%) from 66 institutions completed the training successfully. Of the trainees, 37% were Social Scientists, 34% were Medical/Nursing/Clinical Officers, 5.8% were Statisticians, while 23% belonged to other professions. Majority of the trainees (80%) were employed by Non-Government Organizations while 20% worked with the public health sector. Trainees implemented 66 projects which addressed issues such as improving access to health care services; reducing waiting time for patients; strengthening M&E systems; and improving data collection and reporting. The projects implemented aimed to improve trainees’ skills and competencies in M&E and CQI and the design of the projects was such that they could share these skills with other staff, with minimal interruptions of their work. CONCLUSIONS: The modular, work-based training model strengthens the capacity of the health workforce through hands-on, real-life experiences in the work-setting and improves institutional capacity, thereby providing a practical example of health systems strengthening through health workforce capacity building.